0155 A Double-loop Audit On The Implementation Of The #hellomynameis Twitter Campaign In The Head And Neck Clinic And Its Impact On The Nhs Friends And Family Test. (1st November 2014) - Kuet, Mong-Loon; Stapleton, Emma
Abstract : Background: Kate Granger, a doctor and terminally ill cancer patient, introduced the #hellomynameis Twitter campaign in 2013, as 'the first rung on the ladder to providing compassionate care'. Her campaign defines a gold standard whereby NHS staff should introduce themselves to every patient they meet. The campaign was included in the Government response to the Francis report and is supported by the GMC and NHS England. 1 The purpose of this audit was to implement #hellomynameis in our Department, and to measure its effect with the Friends and Family Test (FFT) – the biggest assessment of patient satisfaction used by the NHS. Methodology: Double-loop audit with educational intervention. 100 consultations were observed in the head and neck clinic. Adherence to the #hellomynameis standard (incidence of clinicians saying hello, their name and job) and FFT scores was recorded. The #hellomynameis campaign and first cycle results were presented locally. 100 further outpatient consultations were then observed. Results: Following implementation of #hellomynameis, the percentage of doctors saying hello, their name and job increased from 67%, 56% and 16% to 100%, 100% and 97% respectively. The FFT score increased dramatically from 38 to 89. Conclusions: The implementation of #hellomynameis in a busy head and neck clinic significantly improved patient satisfaction. #hellomynameis is an effective tool for doctors to adopt a compassionate, patient-centred approach to care, a key recommendation of the Francis report. Nationwide implementation of #hellomynameis will also be of relevance to NHS Trusts due to the FFT's role as a national quality improvement (CQUIN) goal. Reference: hellomynameis, (2014). Government response to the Francis report. [Online]. Available from: http://hellomynameis.org.uk/support . [Accessed: 10th June 2014]